Researches of peak analog modulation of semi-conductor lasers in view of effects of ageing - Олійник, В.І.; Олійник, Є.І.; Шмаров, В.М. (Proceedings of National Aviation University (archive), 2004)
Are investigated amplitude - frequency characteristics of injection semi-conductor lasers. Measurements of factors of nonlinear distortions and depths of peak modulation of such lasers in a current mode the microwave modulation are executed. Experimental researches are carried out with use of semi-conductor lasers after their long warehousing modeling effects of ageing.